Confined range assembly method of superstructure magnetic material and product

By covering Fe-3+ onto the surface of carbon cluster particles and assembling the domain, superstructure magnetic materials with high reflection loss and low dielectric constant were prepared, which solved the problem of insufficient absorption performance of magnetic carbon superstructure in the prior art, and achieved excellent microwave absorption and radar cross-section attenuation effects.

CN119730218AActive Publication Date: 2025-03-28XI AN JIAOTONG UNIV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202411914716.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-28
Estimated Expiration
2044-12-24

AI Technical Summary

Technical Problem

The prior art is difficult to effectively build a magnetic carbon superstructure, resulting in insufficient reflection loss and high dielectric constant, making it difficult to meet the development requirements of electromagnetic wave absorption.

Method used

By covering Fe-3+ onto the surface of carbon cluster particles, assembled into a spherical superstructure, and preparing superstructure magnetic materials through a domain-limited assembly method, the characteristics of high reflection loss and low dielectric constant are achieved.

Benefits of technology

The prepared superstructure magnetic material has excellent microwave absorption capacity and radar cross-section attenuation capacity, reflective loss reaches -62.23dB, and has a low dielectric constant. It is suitable for wave absorbing materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119730218A_ABST
    Figure CN119730218A_ABST
Patent Text Reader

Abstract

The invention discloses a confinement assembly method of a superstructure magnetic material and a product, the method comprises the following steps: mixing natural plant saccharides, long-chain charged supermolecules and an HCl solution for reaction, and calcining to obtain carbon cluster particles; then under the action of long-chain charged supramolecules, Fe < 3 + > covers the surfaces of carbon cluster particles, a spherical upper-layer structure, namely a carbon material containing Fe < 3 + >, is assembled, and the carbon material containing Fe < 3 + > is subjected to secondary calcination to obtain a magnetic carbon spherical upper-layer structure, namely a superstructure magnetic material; the superstructure magnetic material prepared by the confinement assembly method has the characteristics of high reflection loss, low dielectric constant and good uniformity and dispersity, has excellent microwave absorption capability and radar cross section attenuation capability, and can be used as a wave-absorbing material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave absorbing materials, and in particular relates to a confined area assembly method and product of a superstructure magnetic material. Background Art

[0002] With the rapid development of electronic information technology, electromagnetic wave absorbing materials have gradually become an important part of communication information processing technology and military stealth defense systems. Magnetic nanomaterials have high saturation magnetization, low coercivity and high complex magnetic permeability, and have strong magnetic loss capacity, and can be used as microwave absorbing materials. In particular, magnetic carbon composites have the characteristics of both magnetic loss and dielectric loss, low density, large specific surface area, high porosity, and good structural adjustability, and have great application potential in electromagnetic wave absorption. However, due to the lack of synthesis methods, constructing magnetic carbon superstructures from molecules is still a major challenge in materials science.

[0003] At present, Li et al. (Li, X.; Zhou, H.; Zhang, J.; Zhang, X.; Li, M.; Zhang, J.; Darwish, M. A; Zhou, T.; Sun, S.-K.; Xie, L.; Zhou, D., Construction of Shell-like Carbon Superstructures through Anisotropically Oriented Self-assembly for Distinct Electromagnetic Wave Absorption. J. Mater. Chem. A 2024, 12 (7), 4057-4066.) proposed a shell-like carbon superstructure composed of nanorods, but the reflection loss (RL) was only -49.14 dB, and the attenuation mechanism of the shell-like carbon superstructure was single and the dielectric constant was high, which made it difficult to meet the development requirements. Summary of the invention

[0004] In order to overcome the above-mentioned shortcomings of the prior art, the object of the present invention is to provide a method and product for confined assembly of superstructure magnetic materials by -3+ Cover the surface of carbon cluster particles and assemble into a spherical superstructure, that is, Fe -3+ Carbon materials containing Fe -3+ The carbon material is calcined to finally synthesize a magnetic carbon spherical superstructure, namely a superstructure magnetic material; the superstructure magnetic material prepared by the confined assembly method of the present invention has the characteristics of high reflection loss and low dielectric constant, and can be used as an absorbing material.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A method for confined assembly of a superstructure magnetic material comprises the following steps:

[0007] Step 1: Stirring natural plant sugars as reactants, long-chain charged supramolecules as templates, and HCl solution at room temperature to obtain a reaction solution; heating the reaction solution in a water bath to perform polymerization reaction, and obtaining a high molecular weight polymer after cooling to room temperature; in terms of mass volume ratio, natural plant sugars: long-chain charged supramolecules: HCl solution = (1-30) g: (2-20) g: (10-200) mL;

[0008] Step 2: The high molecular polymer obtained in step 1 is centrifugally cleaned, dried, and ground to obtain polymer particles with cluster structure;

[0009] Step 3: calcining the polymer particles obtained in step 2 at 300-900° C. for 3-8 hours in an inert atmosphere, and obtaining carbon cluster particles after cooling to room temperature;

[0010] Step 4: Add the carbon cluster particles obtained in step 3 to a ferric nitrate solution with a mass concentration of 0.08-0.4 g / mL for ultrasonic dispersion to obtain a suspension; age the suspension under magnetic stirring at room temperature, and obtain Fe-containing -3+ Carbon materials;

[0011] Step 5: The Fe-containing -3+ The carbon material is subjected to secondary calcination to obtain magnetic carbon particles, namely, superstructured magnetic materials.

[0012] In the step 1, the mass-to-volume ratio is: natural plant sugar: long-chain charged supramolecule: HCl solution = (5-20) g: (5-10) g: (50-100) mL.

[0013] The natural plant sugar is one of glucose, xylose, sucrose, lactose, fructose, ribose, starch, and cellulose; the long-chain charged supramolecule is one of polymaleic acid, poly(methyl vinyl ether-co-maleic acid), poly(styrene-co-maleic acid) sodium, and poly(4-styrenesulfonic acid-co-maleic acid) sodium; and the molar concentration of the HCl solution is 0.15 mol / L.

[0014] In the step 1, the stirring time is 1-2 hours, and the stirring speed is 600-800 r / min; the reaction temperature is 60-80° C., and the reaction time is 6-12 hours.

[0015] The rotation speed of the centrifugal washing in step 2 is 8000-10000 r / min. Deionized water and anhydrous ethanol are used for centrifugal washing in sequence during the centrifugal process. The washing times are at least three times. The particles are dried at 50-70° C. overnight and then ground for 1-2 hours to obtain polymer particles with cluster structure.

[0016] In step 3, the calcination temperature is 400-700° C. and the calcination time is 4-6 hours; the inert atmosphere is nitrogen or argon.

[0017] The mass concentration of the ferric nitrate solution in step 4 is 0.12-0.24 g / mL.

[0018] The ultrasonic dispersion time in step 4 is 15-30 minutes, and the aging time is 3-12 hours.

[0019] In step 5, the secondary calcination temperature is 300-800° C. and the time is 3-6 hours.

[0020] The present invention also provides a superstructure magnetic material prepared by a confined assembly method of a superstructure magnetic material.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention adopts Fe -3+ The surface of spherical carbon cluster particles is modified so that each spherical carbon cluster particle can be regarded as an independent closed space. Compared with the common carbon absorbing materials, the attenuation mechanism is not single, and the well-dispersed homogeneous magnetic carbon particles greatly improve the unfavorable condition of local impedance matching imbalance caused by the aggregation of magnetic components due to the intrinsic magnetism, making the dielectric constant of magnetic carbon particles lower. At the same time, this superstructure magnetic material has excellent microwave absorption ability (RL min -62.23dB) and radar cross section attenuation capability (RCS is 16.80dB m 2 ), can be used as absorbing material.

[0023] 2. The present invention can achieve controllable carbonization degree of the material by setting a suitable calcination temperature, and form magnetic carbon particles with a spherical cluster structure, i.e., a superstructured magnetic material, by ultrasonic dispersion in a ferric nitrate solution. The obtained material has the characteristics of good uniformity and dispersibility, narrow size distribution range, good stability, and easy surface modification. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The Fe-containing -3+ SEM image of carbon material.

[0025] Figure 2This is a TEM image of the magnetic carbon particles prepared in Example 1, wherein: Figure 2 (a) is at low resolution. Figure 2 (b) is at high resolution.

[0026] Figure 3 This is the TEM image of the magnetic carbon particles prepared in Example 2.

[0027] Figure 4 This is the TEM image of the magnetic carbon particles prepared in Example 3.

[0028] Figure 5 This is the TEM image of the magnetic carbon particles prepared in Example 4.

[0029] Figure 6 This is the TEM image of the magnetic carbon particles prepared in Example 5.

[0030] Figure 7 This is the TEM image of the magnetic carbon particles prepared in Comparative Example 1.

[0031] Figure 8 This is the TEM image of the magnetic carbon particles prepared in Comparative Example 2.

[0032] Fig. 9 This is the TEM image of the carbon particles prepared in Comparative Example 3.

[0033] Fig.10 is a reflection loss diagram of the magnetic carbon particles prepared in Example 1, wherein: Fig.10 (a) is a 3D schematic diagram of reflection loss. Fig.10 (b) is a 2D schematic diagram of reflection loss. Fig.10 (c) is the simulated RCS curve. DETAILED DESCRIPTION

[0034] The technical scheme of the present invention is further described below in conjunction with the accompanying drawings and specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. In addition, it should be understood that after reading the contents of the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms also fall within the scope defined by the claims attached to the present application.

[0035] The following examples use conventional instruments and equipment in the art. Experimental methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.

[0036] A method for confined assembly of a superstructure magnetic material, comprising the following steps:

[0037] Step 1: Stir natural plant sugars as reactants, long-chain charged supramolecules as templates and 0.15 mol / L HCl solution at room temperature for 1-2 hours to obtain a reaction solution; the stirring speed is 600-800 r / min; pour the reaction solution into a 100 mL stainless steel reactor, and place it in an electric blast drying oven to perform a polymerization reaction through water bath heating, and after the stainless steel reactor is cooled to room temperature, a high molecular polymer is obtained; the reaction temperature is 60-80° C., and the reaction time is 6-12 hours;

[0038] By mass volume ratio, natural plant sugar: long chain charged supramolecule: HCl solution = (1-30) g: (2-20) g: (10-200) mL, preferably (5-20) g: (5-10) g: (50-100) mL;

[0039] The natural plant sugar is one of glucose, xylose, sucrose, lactose, fructose, ribose, starch and cellulose; the long-chain charged supramolecule is one of polymaleic acid, poly(methyl vinyl ether-co-maleic acid), poly(styrene-co-maleic acid) sodium and poly(4-styrene sulfonic acid-co-maleic acid) sodium;

[0040] Step 2: The high molecular polymer obtained in step 1 is centrifugally cleaned, dried, and ground to obtain polymer particles with cluster structure;

[0041] After the stainless steel reactor is cooled to room temperature, a high-speed centrifuge is used for centrifugal cleaning at 8000-10000 r / min, and deionized water and anhydrous ethanol are used for centrifugal cleaning in sequence during the centrifugal process. The cleaning times are at least three times, and the reaction mixture is dried at 50-70° C. overnight, and then ground for 1-2 hours to uniformly disperse the polymer particles to obtain polymer particles with cluster structure.

[0042] Step 3: placing the polymer particles obtained in step 2 in a crucible, placing it in a tubular furnace filled with inert gas, heating it to 300-900°C at a heating rate of 2°C / min for calcination, and keeping it at this temperature for 3-8h, and obtaining carbon cluster particles after cooling to room temperature; the inert gas is nitrogen or argon; the calcination temperature is preferably 400-700°C, and the time is preferably 4-6h;

[0043] Step 4: Add the carbon cluster particles obtained in step 3 to the ferric nitrate solution and ultrasonically disperse for 15-30 minutes to obtain a suspension; age the suspension under magnetic stirring at room temperature for 3-12 hours, and obtain Fe-containing -3+ Carbon materials;

[0044] The preparation process of the ferric nitrate solution is as follows: dissolving ferric nitrate powder in a mixed solution of distilled water and anhydrous ethanol, wherein the volume ratio of the distilled water to the anhydrous ethanol is 1:1, and the mass concentration of the ferric nitrate solution is 0.08-0.4 g / mL, preferably 0.12-0.24 g / mL;

[0045] Step 5: The Fe-containing -3+ The carbon material is heated to 300-800°C at a heating rate of 2°C / min and then subjected to secondary calcination to obtain magnetic carbon particles, i.e., superstructured magnetic materials; the secondary calcination time is 3-6h.

[0046] In the above technical scheme, natural plant sugars are first used as reactants, HCl solution is used as a reaction solvent, and long-chain charged supramolecules are used as templates for reaction. As the reaction proceeds, sugars first generate oligomers through decomposition and polymerization, and then gradually grow into smaller polymer particles. At the same time, long-chain charged supramolecules will attach to the surface of small particles through covalent bonds, electrostatic interactions, hydrogen bonds, Coulomb forces, etc., and form a protective layer at the interface between polymer particles and reaction solvents. On the one hand, long-chain charged supramolecules control the growth rate of polymer particles through spatial confinement, so that they maintain a relatively slow but relatively consistent growth rate, ensuring that the size distribution is in an extremely narrow range; on the other hand, through spatial confinement and electrostatic repulsion, smaller polymer particles at high concentrations are prevented from adhering due to high surface energy, ensuring excellent dispersion of particles and high yield and output. By adopting a simple interface confinement method, polymer particles with good dispersibility and narrow size distribution can be efficiently synthesized, and the size can be precisely adjusted by the precursor concentration, the concentration of long-chain charged supramolecular molecules, etc., and high-quality carbon particles can be obtained by high-temperature treatment of polymer particles, and the degree of carbonization can be controlled by the reaction temperature. Then, under the action of polyelectrolyte (long-chain charged supramolecular molecules), Fe -3+ Cover the surface of carbon cluster particles and assemble into a spherical superstructure, that is, Fe -3+ Carbon materials containing Fe -3+ The carbon material is calcined and finally a magnetic carbon spherical superstructure, namely a superstructure magnetic material, is synthesized.

[0047] Example 1

[0048] A method for confined assembly of a superstructure magnetic material, comprising the following steps:

[0049] Step 1: Weigh 10.0g of glucose and 6.0g of polymaleic acid and add them to 50.0mL of 0.15mol / L HCl solution, and stir at 800r / min for 2h until the solution is clear; then pour the reaction solution into a 100mL stainless steel reactor, and place it in an electric blast drying oven to perform a polymerization reaction by water bath heating, and after the stainless steel reactor is cooled to room temperature, a high molecular polymer is obtained; the reaction temperature is 80°C and the reaction time is 8h;

[0050] Step 2: The high molecular weight polymer obtained in step 1 is centrifuged and washed at 9000 r / min, and deionized water and anhydrous ethanol are used to wash three times in sequence during the centrifugation process, dried at 70° C. overnight, and then ground for 1 hour to make the polymer particles evenly dispersed to obtain polymer particles with cluster structure;

[0051] Step 3: 1.0 g of the polymer particles obtained in step 2 was placed in a crucible, placed in a tubular furnace filled with nitrogen, heated to 400°C at a heating rate of 2°C / min for calcination, and kept at this temperature for 6 hours, and then cooled to room temperature to obtain carbon cluster particles;

[0052] Step 4: Take 0.5 g of the carbon cluster particles obtained in step 3 and add them to 20 ml of 0.24 g / mL ferric nitrate solution for ultrasonic dispersion for 15 min to obtain a suspension; age the suspension under magnetic stirring at room temperature for 5 h, and wash and dry to obtain Fe-containing -3+ Carbon materials;

[0053] Step 5: The Fe-containing -3+ The carbon material is placed in a crucible, put into a tubular furnace filled with nitrogen, calcined to 450°C at a heating rate of 2°C / min for secondary calcination, and kept at this temperature for 6 hours. After cooling to room temperature, magnetic carbon particles, i.e., superstructured magnetic materials, are obtained.

[0054] Figure 1 The Fe-containing -3+ SEM image of carbon material, Figure 1 It can be seen that Fe -3+ The carbon material has a spherical cluster structure with good uniformity and high dispersion, a smooth surface, and a diameter of about 4 microns.

[0055] Figure 2 This is a TEM image of the magnetic carbon particles prepared in Example 1, wherein: Figure 2 (a) is at low resolution, where Figure 2 (b) is at high resolution; Figure 2 (a) It can be seen that the magnetic carbon particles obtained after high temperature calcination have a spherical cluster structure, which is similar to Figure 1 Fe-3+ Compared with the carbon materials, the original spherical cluster structure is maintained, and the uniformity and dispersion are good, and the size is slightly reduced; Figure 2 (b) It can be seen that nanometer-scale Fe3O4 particles are generated on the surface of the spherical cluster structure and are evenly dispersed.

[0056] Example 2

[0057] A method for confined assembly of a superstructure magnetic material, comprising the following steps:

[0058] Step 1: Weigh 20.0g xylose and 5.0g poly(methyl vinyl ether copolymer maleic acid) and add them into 100.0mL 0.15mol / L HCl solution, and stir at 600r / min for 1h until the solution is clear; then divide the reaction solution equally and pour it into a 100mL stainless steel reactor, and place it in an electric blast drying oven and heat it in a water bath to perform polymerization reaction, and after the stainless steel reactor is cooled to room temperature, a high molecular polymer is obtained; the reaction temperature is 60°C and the reaction time is 6h;

[0059] Step 2: The high molecular weight polymer obtained in step 1 is centrifuged and washed at 8000 r / min, and deionized water and anhydrous ethanol are used to wash three times in sequence during the centrifugation process, dried at 50° C. overnight, and then ground for 1 hour to make the polymer particles evenly dispersed to obtain polymer particles with cluster structure;

[0060] Step 3: 1.0 g of the polymer particles obtained in step 2 was placed in a crucible, placed in a tubular furnace filled with nitrogen, heated to 700°C at a heating rate of 2°C / min for calcination, and kept at this temperature for 4 hours, and then cooled to room temperature to obtain carbon cluster particles;

[0061] Step 4: Take 0.5 g of the carbon cluster particles obtained in step 3 and add them to 20 mL of 0.12 g / mL ferric nitrate solution for ultrasonic dispersion for 30 min to obtain a suspension; age the suspension under magnetic stirring at room temperature for 3 h, and obtain Fe-containing -3+ Carbon materials;

[0062] Step 5: The Fe-containing -3+ The carbon material is placed in a crucible, put into a tubular furnace filled with nitrogen, heated to 800°C at a heating rate of 2°C / min for secondary calcination, and kept at this temperature for 3 hours. After cooling to room temperature, magnetic carbon particles, i.e., superstructured magnetic materials, are obtained.

[0063] Figure 3 TEM image of the magnetic carbon particles prepared in Example 2; Figure 3It can be seen that the magnetic carbon particles have a spherical cluster structure with good uniformity, and the Fe3O4 particles attached to the surface of the spherical cluster structure are dispersed evenly and regularly.

[0064] Example 3

[0065] A method for confined assembly of a superstructure magnetic material, comprising the following steps:

[0066] Step 1: Weigh 5.0g of ribose and 10.0g of poly(methyl vinyl ether copolymer maleic acid) and add them to 80.0mL of 0.15mol / L HCl solution, and stir at 650r / min for 2h until the solution becomes clear; then pour the reaction solution into a 100mL stainless steel reactor, and place it in an electric blast drying oven and heat it in a water bath to perform a polymerization reaction, and after the stainless steel reactor is cooled to room temperature, a high molecular polymer is obtained; the reaction temperature is 70°C and the reaction time is 12h;

[0067] Step 2: The polymer obtained in step 1 is centrifuged and washed at 10000 r / min, and deionized water and anhydrous ethanol are used to wash three times in sequence during the centrifugation process, dried at 60° C. overnight, and then ground for 2 hours to make the polymer particles evenly dispersed to obtain polymer particles with cluster structure;

[0068] Step 3: 1.0 g of the polymer particles obtained in step 2 was placed in a crucible, placed in a tubular furnace filled with nitrogen, heated to 300° C. at a heating rate of 2° C. / min for calcination, and kept at this temperature for 5 h. After cooling to room temperature, carbon cluster particles were obtained;

[0069] Step 4: Take 0.5 g of the carbon cluster particles obtained in step 3 and add them to 20 mL of 0.08 g / mL ferric nitrate solution for ultrasonic dispersion for 15 min to obtain a suspension; age the suspension under magnetic stirring at room temperature for 12 h, and obtain Fe-containing -3+ Carbon materials;

[0070] Step 5: The Fe-containing -3+ The carbon material is placed in a crucible, put into a tubular furnace filled with nitrogen, heated to 300°C at a heating rate of 2°C / min for secondary calcination, and kept at this temperature for 4 hours. After cooling to room temperature, magnetic carbon particles, i.e., superstructured magnetic materials, are obtained.

[0071] Figure 4 TEM image of the magnetic carbon particles prepared in Example 3; Figure 4 It can be seen that the magnetic carbon particles have a spherical cluster structure with good uniformity and high dispersibility; nano-scale Fe3O4 particles are evenly dispersed on the surface of the spherical cluster structure.

[0072] Example 4

[0073] A method for confined assembly of a superstructure magnetic material, comprising the following steps:

[0074] Step 1: Weigh 10.0g lactose and 8.0g poly(styrene-co-maleic acid) sodium, add them into 50.0mL 0.15mol / L HCl solution, and stir at 800r / min for 2h until the solution becomes clear; pour the reaction solution into a 100mL stainless steel reactor, and place it in an electric blast drying oven to perform a polymerization reaction by water bath heating, and after the stainless steel reactor is cooled to room temperature, a high molecular polymer is obtained; the reaction temperature is 65°C, and the reaction time is 10h;

[0075] Step 2: The high molecular weight polymer obtained in step 1 is centrifuged and washed at 8500 r / min, and deionized water and anhydrous ethanol are used to wash three times in sequence during the centrifugation process, and then dried at 55° C. overnight, and then ground for 1 hour to make the polymer particles evenly dispersed to obtain polymer particles with cluster structure;

[0076] Step 3: 1.0 g of the polymer particles obtained in step 2 was placed in a crucible, placed in a tubular furnace filled with nitrogen, heated to 900°C at a heating rate of 2°C / min for calcination, and kept at this temperature for 6 hours, and then cooled to room temperature to obtain carbon cluster particles;

[0077] Step 4: Take 0.5 g of the carbon cluster particles obtained in step 3 and add them to 20 mL of 0.4 g / mL ferric nitrate solution for ultrasonic dispersion for 20 min to obtain a suspension; age the suspension under magnetic stirring at room temperature for 7 h, and obtain Fe-containing -3+ Carbon materials;

[0078] Step 5: The Fe-containing -3+ The carbon material is placed in a crucible, put into a tubular furnace filled with nitrogen, heated to 600°C at a heating rate of 2°C / min for secondary calcination, and kept at this temperature for 5 hours. After cooling to room temperature, magnetic carbon particles, i.e., superstructured magnetic materials, are obtained.

[0079] Figure 5 TEM image of the magnetic carbon particles prepared in Example 4; Figure 5 It can be seen that the magnetic carbon particles have a spherical cluster structure with good uniformity and significantly large dispersion gaps, indicating that the dispersibility is greatly improved; in addition, nano-scale Fe3O4 particles are uniformly dispersed on the surface of the spherical cluster structure.

[0080] Example 5

[0081] A method for confined assembly of a superstructure magnetic material, comprising the following steps:

[0082] Step 1: Weigh 15.0g of fructose and 6.0g of sodium poly(4-styrenesulfonic acid-co-maleic acid) and add them to 70.0mL of 0.15mol / L HCl solution, and stir at 700r / min for 1h until the solution becomes clear; pour the reaction solution into a 100mL stainless steel reactor, and place it in an electric blast drying oven and heat it in a water bath to perform a polymerization reaction, and after the stainless steel reactor is cooled to room temperature, a high molecular polymer is obtained; the reaction temperature is 75°C and the reaction time is 8h;

[0083] Step 2: The high molecular weight polymer obtained in step 1 is centrifuged and washed at 9500 r / min, and deionized water and anhydrous ethanol are used to wash three times in sequence during the centrifugation process, dried at 65° C. overnight, and then ground for 1 hour to make the polymer particles evenly dispersed to obtain polymer particles with cluster structure;

[0084] Step 3: 1.0 g of the polymer particles obtained in step 2 was placed in a crucible, placed in a tubular furnace filled with nitrogen, heated to 500° C. at a heating rate of 2° C. / min for calcination, and kept at this temperature for 4 h. After cooling to room temperature, carbon cluster particles were obtained;

[0085] Step 4: Take 0.5 g of the carbon cluster particles obtained in step 3 and add them to 20 mL of 0.32 g / mL ferric nitrate solution for ultrasonic dispersion for 25 min to obtain a suspension; age the suspension under magnetic stirring at room temperature for 10 h, and obtain Fe-containing -3+ Carbon materials;

[0086] Step 5: The Fe-containing -3+ The carbon material is placed in a crucible, put into a tubular furnace filled with nitrogen, heated to 500°C at a heating rate of 2°C / min for secondary calcination, and kept at this temperature for 6 hours. After cooling to room temperature, magnetic carbon particles, i.e., superstructured magnetic materials, are obtained.

[0087] Figure 6 is a TEM image of the magnetic carbon particles prepared in Example 5; Figure 6 It can be seen that the magnetic carbon particles have a spherical cluster structure with good uniformity and significantly large dispersion gaps, indicating that the dispersibility is greatly improved; in addition, nano-scale Fe3O4 particles are uniformly dispersed on the surface of the spherical cluster structure.

[0088] Comparative Example 1

[0089] The process and parameters of this comparative example 1 are the same as those of Example 1, except that the first calcination process of step 3 is omitted to obtain magnetic carbon particles such as Figure 7 As shown, Figure 2Compared with (b), the Fe3O4 particles generated on the surface of magnetic carbon particles are significantly reduced and their size is also smaller.

[0090] Comparative Example 2

[0091] The process and parameters of this comparative example 2 are the same as those of Example 1, except that: the mass of the polymaleic acid weighed in step 1 is 1.0 g, and the magnetic carbon particles are prepared as follows: Figure 8 As shown, when the input mass of polymaleic acid is 1.0g, the prepared magnetic carbon particles obviously show irregular cluster shapes, the clusters are of different sizes, the uniformity is very poor, and the dispersion gap is small, and the dispersion is also very poor.

[0092] Comparative Example 3

[0093] The process and parameters of this comparative example 3 are the same as those of Example 3, except that 0.5 g of the carbon cluster particles obtained in step 3 are added to 20 ml of 0.07 g / mL ferric nitrate solution for ultrasonic dispersion to obtain carbon particles such as Fig. 9 As shown, 0.07 g / mL ferric nitrate solution was used for ultrasonic dispersion. Figure 2 Compared with (b), there is almost no nano-sized Fe3O4 particles generated on the surface of the prepared carbon particles.

[0094] A reflection loss test was performed using a vector network analyzer. 80 mg of the magnetic carbon particles obtained in Example 1 were weighed, mixed with paraffin in a ratio of 1:1, and placed in a mold to form a ring.

[0095] like Fig.10 (a) and Fig.10 (b) shows the reflection loss RL of the magnetic carbon particles prepared in Example 1 of the present invention. min It is -62.23dB and has a wide enough effective absorption bandwidth (EAB). max =4.2GHz, so that effective absorption can be achieved in a wider frequency band; Fig.10 (c) shows that the comparison sample is carbon sphere, and the radar cross-sectional area (RCS) of the magnetic carbon particles is 16.80 dB m 2 , having excellent radar cross section attenuation capability; the surface of the magnetic carbon particles prepared by the present invention is covered with nanometer-level Fe3O4 particles. Since Fe3O4 is a semiconductor material, its radar cross section attenuation capability is stronger than that of the shell-like carbon superstructure in the prior art, so that the dielectric constant of the magnetic carbon particles prepared by the present invention is lower. Therefore, the magnetic carbon material prepared by the present invention can be used as a wave absorbing material, and the absorption effect is very good.

[0096] The above contents are only for explaining the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.

Claims

1. A method for confined assembly of a superstructure magnetic material, characterized in that: The following steps are involved: Step 1: Stirring natural plant sugars as reactants, long-chain charged supramolecules as templates, and HCl solution at room temperature to obtain a reaction solution; heating the reaction solution in a water bath to perform polymerization reaction, and obtaining a high molecular weight polymer after cooling to room temperature; in terms of mass volume ratio, natural plant sugars: long-chain charged supramolecules: HCl solution = (1-30) g: (2-20) g: (10-200) mL; Step 2: The high molecular polymer obtained in step 1 is centrifugally cleaned, dried, and ground to obtain polymer particles with cluster structure; Step 3: calcining the polymer particles obtained in step 2 at 300-900° C. for 3-8 hours in an inert atmosphere, and obtaining carbon cluster particles after cooling to room temperature; Step 4: Add the carbon cluster particles obtained in step 3 to a ferric nitrate solution with a mass concentration of 0.08-0.4 g / mL for ultrasonic dispersion to obtain a suspension; age the suspension under magnetic stirring at room temperature, and obtain Fe-containing -3+ Carbon materials; Step 5: The Fe-containing -3+ The carbon material is subjected to secondary calcination to obtain magnetic carbon particles, namely, superstructured magnetic materials.

2. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: In the step 1, the mass-to-volume ratio is: natural plant sugar: long-chain charged supramolecule: HCl solution = (5-20) g: (5-10) g: (50-100) mL.

3. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: The natural plant sugar is one of glucose, xylose, sucrose, lactose, fructose, ribose, starch, and cellulose; the long-chain charged supramolecule is one of polymaleic acid, poly(methyl vinyl ether-co-maleic acid), poly(styrene-co-maleic acid) sodium, and poly(4-styrenesulfonic acid-co-maleic acid) sodium; and the molar concentration of the HCl solution is 0.15 mol / L.

4. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: In the step 1, the stirring time is 1-2 hours, and the stirring speed is 600-800 r / min; the reaction temperature is 60-80° C., and the reaction time is 6-12 hours.

5. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: The rotation speed of the centrifugal washing in step 2 is 8000-10000 r / min. Deionized water and anhydrous ethanol are used for centrifugal washing in sequence during the centrifugal process. The washing times are at least three times. The particles are dried at 50-70° C. overnight and then ground for 1-2 hours to obtain polymer particles with cluster structure.

6. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: In step 3, the calcination temperature is 400-700° C. and the calcination time is 4-6 hours; the inert atmosphere is nitrogen or argon.

7. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: The mass concentration of the ferric nitrate solution in step 4 is 0.12-0.24 g / mL.

8. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: The ultrasonic dispersion time in step 4 is 15-30 minutes, and the aging time is 3-12 hours.

9. The method for confined assembly of a superstructure magnetic material according to claim 1, characterized in that: In step 5, the secondary calcination temperature is 300-800° C. and the time is 3-6 hours.

10. A superstructure magnetic material prepared by the confined assembly method of a superstructure magnetic material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method and product of shell-like super structure carbon material

    CN107522189A

  • Preparation method of monodisperse agarose superparamagnetic micro-sphere

    CN108250495A

  • Solid Fe3O4@C superstructure microsphere wave-absorbing material and preparation method and application thereof

    CN111234776A

  • Metamaterial wave absorber

    CN112332108A

  • Two-dimensional carbon nitride supported iron monatomic catalyst as well as preparation method and application thereof

    CN114177927A